Pengaruh Variasi Fraksi Volume Serbuk Alumina Terhadap Kekuatan Tarik Dan Kekerasan Pada Aluminium 1050 - Mohammad Andrea Iswanto; Irwan Aranda (TURBO [Tulisan Riset Berbasis Online], 2026)
Aluminum 1050 is a material with low density, good corrosion resistance, and excellent formability; however, it possesses relatively low mechanical strength and hardness. One approach to improving its mechanical properties is the addition of alumina (Al₂O₃) powder as a reinforcing material to form a Metal Matrix Composite (MMC). This study aims to investigate the effect of alumina powder volume fractions of 0%, 3%, 6%, and 9% on the tensile strength and hardness of Aluminum 1050 produced using the stir casting method. The melting process was carried out at approximately 700°C, while the alumina powder was preheated at 400°C for 30 minutes. The molten metal was then stirred for 5 minutes before being poured into the mold. Mechanical properties were evaluated using a Universal Testing Machine (UTM) for tensile testing and a Brinell Hardness Tester for hardness testing. The tensile test results showed that the highest average tensile strength was obtained at a 3% alumina volume fraction, reaching 52.27 MPa, followed by 6% at 50.01 MPa, 0% at 43.90 MPa, and 9% at 20.68 MPa. Meanwhile, the average hardness values were 88.33 HBN, 112.41 HBN, 115.48 HBN, and 113.59 HBN for the 0%, 3%, 6%, and 9% alumina volume fractions, respectively. The results indicate that the addition of alumina powder improves the mechanical properties of Aluminum 1050. The optimum tensile strength was achieved at a 3% alumina volume fraction, while the highest hardness value was obtained at a 6% alumina volume fraction. Excessive alumina addition may reduce the material strength due to non-uniform particle distribution and the formation of porosity.